Respostas

2014-07-06T14:36:18-03:00
Vamos identificar os valores a e b da função:

f(x) = 7x - 3
f(x) = ax + b

a = 7
b = -3

f(a+b) = f(7-3) = f(4)

f(x) = 7x-3

f(4) = 7.4 - 3

f(4) = 28 - 3

f (4) = 25
1 5 1
2014-07-06T15:57:58-03:00
F(x)=7x -3                                                                                                                                                    f(x) = ax+b                                                                                                                                                a=7     b=-3                                                                                                                                                        f(x)=7x-3                                                                                                                                                  f(4)=7*4-3                                                                                                                                              f(4)=28-3=                                                                                                                                                 f(4)=25
1 5 1